Unlawful combatants: a genealogy of the irregular fighter - Scheipers, Sibylle (Oxford University Press, 2015)
The book investigates the emergence and the development of irregular fighters, such as guerrillas, rebels, insurgents, and terrorists throughout the history of modern war. It presents a historically based critique of the twenty-first century notion of the irregular fighter as an 'unlawful combatant'.